Participatory Budgeting: A Librarian’s Experience - John DeLooper (The Political Librarian, 2021)
This article discusses one librarian’sexperience with the Participatory Budgeting process in New York City. Itincludes information about how New York’s Participatory Budgeting processworks, as well as Participatory Budgeting’s principles, and some discussion ofhow libraries have utilized PB. In addition, it includes discussion of howlibrarian skillsets can be especially useful for participatory budgeting.
Keywords: Participatory Budgeting; Civic Engagement; New York City